Gemblak stereotype film “kucumbu tubuh indahku” by Garin Nugroho - Oki, oki cahyo nugroho; Ridwan , Ridwan Yudha Pratama (COMMICAST, 2022)
Film is one of the electronic media that has a huge appeal among the public. Films also play an active role in conveying messages or information, but with very neat packaging. Make the message or information more interesting and entertain the audience. Based on this, many films always contain events or phenomena, one of which is the film "A Memories of My Body". Where this film tells the story of LGBT people and is associated with ancient culture, namely the Lengger and Gemblak dances, this paper aims to find out the analysis of William Gamson and Andre Modigliani's framing of the Gemblak stereotype in the film "A Memories of My Body," which was made by Garin Nugroho and released on April 18, 2019. The theory used is framing analysis from William Gamson and André Modigliani. The methodology used in this research is descriptive qualitative. The data analysis technique uses the Umberto Eco concept by determining the framing device (metaphor, exemplar, catchphrase, depiction, visual image). ) and tools of reasoning (roots, principle of appeal, consequences).The results show that in the film "A Memoir of My Body" by Garin Nugroho there is a depiction of Gemblak as a sexual deviation and feminism, which can lead to public opinion.